DNA polymerase I modulates inducible stable DNA replication in Escherichia coli. - Ruscitti, T (1992)
Mutants of Escherichia coli lacking RNase HI activity and cells induced for the SOS response express modes of DNA replication independent of protein synthesis, called constitutive and induced stable DNA replication, respectively. We report here that mutants deleted for the polA gene express induced stable DNA replication at approximately 25-fold the rate of wild-type cells, whereas constitutive stable DNA replication is not enhanced.